REDUCING PAIN IN INVASIVE PROCEDURES: THE IMPACT OF PUZZLE PLAY THERAPY ON PEDIATRIC URINARY TRACT INFECTION PATIENTS - Kuswandari, Kuswandari; Margaretha, Sumarti Endah Purnamaningsih Maria (Medical-Surgical Journal of Nursing Research, 2024)
Urinary tract infection is an infection that affects the upper urinary tract (kidneys and ureters) and the lower part (vesica urinaria and urethra). Pain is an unpleasant experience for both children and adults who will groan in pain. Invasive procedures are medical procedures that injure human body parts. To reduce pain in children after invasive procedures are carried out, namely by non-pharmacological therapy, namely puzzle playing therapy. Puzzle play therapy is a game that is composed of pieces of messy pictures into a whole picture. To describe the application of efforts to reduce pain in invasive procedures with puzzle play therapy in urinary tract infection patients at Dr. RSUP. Sardjito Yogyakarta. The method used in this case study is descriptive method The focus of the study was children aged 3-4 years after the child received an invasive procedure in the form of an intravenous plug for 15 minutes. Respondents amounted to one can be female or male. Data was collected through interviews, observations, standard operating procedure sheets and observation sheets using the wong baker pain scale, namely FACES. The results showed that there was a decrease in the pain scale on the first day from 5 to 4, on the second day from 5 to 3, on the third day from 4 to 2. Puzzle play therapy is effective in reducing invasive procedure pain in children with urinary tract infections.